2000
DOI: 10.1021/a1000017p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fluorescence, Phosphorescence, and Chemiluminescence Spectrometry

Abstract: This review covers the approximately two-year period since our last review (A1), roughly from November 1997 through October 1999. A computer search of Chemical Abstracts provided most of the references for this review. Coverage is limited to articles that describe new developments in the theory and practice of molecular luminescence for chemical analysis in the ultravioletvisible and near-infrared region.Citations may be duplicated between sections due to articles with contents that span several topics. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 132 publications
0
36
0
1
Order By: Relevance
“…38-41 Since 100 mol % borate is required to observe such behavior (or 100 mol % pH chromoionophore; see below), initial conditioning of the films in buffer leads to all of the TFPB anions serving as counter-ions to 100 % of the Al[OEP] in monomeric form (as Al[OEP] + ) and hence the very sharp Soret band expected for the monomer species. As fluoride is added to the buffer, fluoride is extracted to serve as an axial ligand to the Al[OEP] + species; however, to maintain charge neutrality in the polymeric film, a dimer in which two fluoride ions are bridging two Al[OEP] complexes appears to form (Al[OEP] F) 2 . If only a single fluoride bridging species were responsible for the dramatic change in UV-VIS spectrum, then 50 mol% TFPB would be the optimal level to stabilize a positively charged (Al[OEP]) 2 F + dimer.…”
Section: Spectral Properties Of Films Doped With Al[oep]mentioning
confidence: 99%
See 1 more Smart Citation
“…38-41 Since 100 mol % borate is required to observe such behavior (or 100 mol % pH chromoionophore; see below), initial conditioning of the films in buffer leads to all of the TFPB anions serving as counter-ions to 100 % of the Al[OEP] in monomeric form (as Al[OEP] + ) and hence the very sharp Soret band expected for the monomer species. As fluoride is added to the buffer, fluoride is extracted to serve as an axial ligand to the Al[OEP] + species; however, to maintain charge neutrality in the polymeric film, a dimer in which two fluoride ions are bridging two Al[OEP] complexes appears to form (Al[OEP] F) 2 . If only a single fluoride bridging species were responsible for the dramatic change in UV-VIS spectrum, then 50 mol% TFPB would be the optimal level to stabilize a positively charged (Al[OEP]) 2 F + dimer.…”
Section: Spectral Properties Of Films Doped With Al[oep]mentioning
confidence: 99%
“…Interestingly, we found that the experimental data obtained for different film compositions and measured at different pH-values or different buffer systems fit very well with the general optode response function assuming a 1 Figures 5A, B, C, and D, as well as Figure 6B for Film-7 formulated with DOS). The theoretical curves in this case can be calculated based on the following general anion-optode response function 13 : (2) where (K ) corresponding to the overall coextraction constant, and α -value (the degree of deprotonation) is the fraction of the total indicator present in the deprotonated form. 13 Although it appears from the spectral data that the Al[OEP]-fluoride interaction is not as simple as that observed for other porphyrin systems, and possibly involves multiple equlibria including the formation of a bis-fluoride bridged porphyrin dimer, the fluoride ion response of the optical sensitive films based on Al[OEP] does follow the classical optode response function for a 1:1 complex formation.…”
Section: Optical Response Of Al[oep]/eth-7075 To Fluoride Ionmentioning
confidence: 99%
“…6 Chemiluminescence (CL) has been exploited with a wide range of applications in different fields, such as biotechnology, pharmacology, molecular biology, and clinical and environmental chemistries. [7][8][9][10] However, only one CL method was reported for the determination of MP, which was based on reactions among tris-(2,2′-bipyridine)ruthenium(II), MP, hydrogen peroxide, Tween 20 and hydroxide ion. 11 In this method, the mixing order of the reagents considerably affects the CL signal.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the advantages of LEDs are compelling. LEDs have now been used in a wide range of optical-sensing devices (Oldham et al 2000;Agbaria et al 2002;Powe et al 2004;Fletcher et al 2006;Lowry et al 2008;Powe et al 2010), and researchers have begun to demonstrate field-capable instruments. For example, Obeidat et al (2008) describe a 1.5 kg spectrofluorometer for analyzing plant and animal feed in the field, using excitation sources ranging from 405 to 640 nm; power is supplied by a laptop computer which also captures, stores, and analyzes the resulting EEMs.…”
mentioning
confidence: 99%